PENGARUH GAYA HIDUP, LOCUS OF CONTROL, DAN PENDAPATAN TERHADAP PERILAKU MANAJEMEN KEUANGAN MAHASISWA - Yuliana Nuraini; Ika Indriasari; Rita Meiriyanti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
The influence of lifestyle, locus of control, and income on financial management behavior. This research aims to analyze and test the influence of lifestyle, locus of control, and income on the financial management behavior of PGRI University Semarang students. This research is a quantitative research with data collection techniques using a questionnaire using the Cochran formula. The sampling technique uses probability sampling testing with proportional random sampling, thereby producing a sample of 100 respondents. Data analysis techniques use instrument tests, classical assumption tests, multiple linear regression tests and hypothesis tests. This research data processing uses the SPSS 26 stone tool. The test results show that lifestyle has a negative and significant effect on students' financial management behavior with a t_count < t_table test value of -3.703 < 1.984 with a significance value of 0.00. The locus of control variable has a positive and significant effect on students' financial management behavior with a test value of t_count > t_table of 20,539 > 1,984 with a significance value of 0.00. and income is proven to have a significant positive effect on students' personal financial management behavior with a test value of t_count > t_table of 7,630 > 1,984 with a significance value of 0.00